Contraindications to punishment In the Iraqi Penal Code No.111 of 1969 as amended - Abbas Adain, Abdulrahman (Journal of College of Education, 2022)
Abstract The research included the most important prohibitions of punishment in the Iraqi Penal Code No. 111 of 1969, which called on the criminal legislator to legislate and put it at the heart of the Iraqi penal code, such as ignorance of the law for foreigners, crimes of criminal agreement, and sheltering the perpetrator by his wife, assets, branches and brothers. And his sisters, the one who is on the false right, and the perpetrator of the crime of kidnapping in the case of marriage to the one who kidnapped her, the crimes of slander and insult between the litigants and the courts to defend their rights, and the reason for the exemption of punishment for the perpetrators of these crimes is the appreciation of the criminal legislator for the higher interests of society and social considerations that The legislator appreciates it, which achieves the interests of society rather than punishing the perpetrator, considering legislation as the tool and means of achieving political, economic and social reform in all countries.